Water Based Coolant sebagai Cairan Pendingin pada Proses Membubut AISI 1045 dengan Mengunakan Pahat Karbida Berlapis - Dikki Yumarsa; Ismet Hari Mulyadi; Dedison Gasni (Forum Kerjasama Pendidikan Tinggi (FKPT), 2026)
This study aims to evaluate the performance of water-based coolant (WBC) formulated with the addition of MXene additives (0.35 wt%), Carboxymethyl Cellulose (CMC, 0.35 wt%), and Span 60 (0.7 wt%) on surface roughness and tool wear during the turning process of AISI 1045 steel using CNMG 120404 coated carbide cutting tools. The research method employed experimental approach by comparing additive-based WBC under Minimum Quantity Lubrication (MQL) system with Dromus coolant, using identical machining parameters. The test results demonstrated that the use of additive WBC produced an average surface roughness of 3.81 µm and tool wear of 38.10 µm, which was superior compared to Dromus coolant that recorded roughness of 5.04 µm and wear of 54.05 µm. Statistical data analysis using paired sample T-test was conducted to determine the effect of surface roughness and tool wear between additive WBC and Dromus. The statistical analysis results showed that the difference was significant (p-value < 0.05) for both roughness and wear parameters. The combination of MXene's thermal properties, CMC's stability, and Span 60's emulsification role proved effective in enhancing cooling and lubrication performance. These findings indicate that additive WBC has the potential to serve as an efficient, economical, and environmentally friendly coolant alternative in conventional machining processes.